2000
DOI: 10.1300/j004v16n01_02
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effects of a Group-Based Horticulture Experience on the Quality of Life of Persons with Chronic Mental Illness

Abstract: The purpose of this research was to study the impact of horticulture, a purposeful activity, on group participants in a clubhouse facility. This impact was analyzed according to Zhan's (1992) conceptual model of quality of life (QOL) which includes: (a) life satisfaction, (b) self-concept, (c) health and functioning, and (d) socio-economic factors. Ten members diagnosed with chronic mental illnesses participated in this 6-week study. This investigation interpreted the description of the horticulture experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 6 publications
2
17
1
Order By: Relevance
“…Engagement in activities that facilitate these dimensions needs to be considered in the rehabilitation of people with stress-related ill health as many of these dimensions are negatively affected (Floderus et al, 2005;Håkansson & Matuska, 2010). For example, women with a stress-related disorder reported that they often had trouble sleeping and experienced everyday occupations as cheerless (Håkansson & Matuska, 2010).…”
mentioning
confidence: 99%
“…Engagement in activities that facilitate these dimensions needs to be considered in the rehabilitation of people with stress-related ill health as many of these dimensions are negatively affected (Floderus et al, 2005;Håkansson & Matuska, 2010). For example, women with a stress-related disorder reported that they often had trouble sleeping and experienced everyday occupations as cheerless (Håkansson & Matuska, 2010).…”
mentioning
confidence: 99%
“…The results from studies regarding the influence of TH on quality of life vary; both nonsignificant (Richards & Kafami, 1999;Sempik, 2007) and significant changes (Heliker, Chadwick, & O'Connell, 2000;Waliczek, Zajicek, & Lineberger, 2005) have been reported. Participants in TH programs have often reported that participating was a positive experience (Fieldhouse, 2003;Perrins-Margalis, 2000;74 M. T. GONZALEZ ET AL. Sempik, Aldridge, & Becker, 2005).…”
mentioning
confidence: 99%
“…Most studies have focused on the use of HT in cancer patients [8,32] (Shin and Park, 2007;Sock and Jung, 2006). Since our study focused on rural women with hope as an endpoint and a comparable study does not exist, it is impossible to compare results; however, hope, social support, and quality of life have meaningful relations [8,33] . HT provides a great opportunity to improve hope and self-esteem by presenting achievements to family members at the end of the program.…”
Section: Discussionmentioning
confidence: 99%